Land regularization in Tijuana, Mexico - Paavo Monkkonen (University of California, Institute of Urban and Regional Development (IURD), 2008)
Land titling programs are increasingly encouraged by international organizations as an essential component of urban policy in developing countries. The clear definition of property rights is argued to be a sine qua non of economic development. However, most academic research on land titles has focused on the impacts of land titles and there is a dearth of analysis of the demand for land titling and the structure of land titling programs. A better understanding of land titling programs is essential for the policy to succeed in improving the lives of people living in informally developed neighborhoods. This paper presents a model of demand for land regularization in Tijuana, Baja California, Mexico. The model adapts previous work on land registration in agricultural areas to regularization in urban areas, incorporating insights on the different sources of value for urban land and titles in urban areas, as well as the characteristics of the regularization process in Mexico. An empirical test of the determinants of success in land titling is conducted using administrative and spatial data from 140 irregularly developed neighborhoods where regularization agencies are active. The prediction of previous modelsthat there should be more land titling for land that is valuabledoes not hold. The results demonstrate inefficiency in the land titling system of Tijuana, inefficiency that is possibly explained by governmental opportunism.
Keywords: 330; Raumordnungsrecht; Kommunalplanung; Bodenreform; Großstadt; Tijuana; Entwicklungsländer